Sonnet to a dead contessa [large type] - Morris, Gilbert (Morris, Gilbert. Lady Trent mysteries, 2009)
Women from the upper end of British society are being targeted by a killer known as The Slasher. When her best friend becomes the latest victim, Lady Trent vows to capture the murderer with the help of her partner Dylan Tremayne. Serafina must rely on her wits and newfound trust in God to save her from a killer known only as "The Slasher" in the story that concludes the Lady Trent Mysteries.